PENGARUH KUALITAS PELAYANAN TERHADAP MINAT BELI PADA MASA PANDEMIK COVID-19 DI KANTIN YUANK KOTA BIMA - Winda Winda; Firmansyah Kusumayadi (Jurnal Ilmiah Manajemen Ubhara, 2021)
Quality of service is one of the main activities carried out by Kantin Yuank in its efforts to develop and earn a profit. Therefore, this study aims to determine the effect of service quality on visitor buying interest during the Covid 19 pandemic at the Yuank Canteen in Bima City. The research method uses quantitative methods with primary data sources. The sample in this study was 96 respondents using non-probability sampling method with accidental sampling technique. The research was conducted by distributing questionnaires. Data analysis in this study includes: validity and reliability tests, simple linear regression, correlation coefficient, determination coefficient (R2) and hypothesis testing through t test. Hypothesis testing using the t test shows that the independent variable quality of service studied is proven to significantly affect the dependent variable consumer purchase interest with a p value of 0.000 less than 0.05 (0.000 <0.05). The Adjusted R Square is 0.251. This means that 25.1% of buying interest is influenced by service quality and the remaining 74.9% is caused by other factors not included in this study such as product quality, price, place and others. The results showed that service quality influenced purchase intention. Thus, by maintaining and improving product quality and service quality at the Yuank Canteen in Bima City, a positive visitor attitude will be formed which will affect the buying interest of visitors at the Yuank Canteen in Bima City.